2019
DOI: 10.1097/shk.0000000000001139
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Implementation of Magnetic Levitation to Quantify Leukocyte Size, Morphology, and Magnetic Properties to Identify Patients With Sepsis

Abstract: Septic patients had circulating leukocytes with especially increased size parameters, which distinguished sepsis from non-infected patients with promising high accuracy. This portal-device compatible technology, shows promise as a potential bedside diagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Median levitation height of circulating leukocytes was measured for 22 infected patients and 39 noninfected control patients, and it was observed that the levitation height was 293.1 ± 61.4 px for septic patients and 288.8 ± 23.7 px for the control group, demonstrating comparable classification performance of the developed MagLev platform. [ 57 ]…”
Section: Emerging End Applications Of Magnetic Levitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Median levitation height of circulating leukocytes was measured for 22 infected patients and 39 noninfected control patients, and it was observed that the levitation height was 293.1 ± 61.4 px for septic patients and 288.8 ± 23.7 px for the control group, demonstrating comparable classification performance of the developed MagLev platform. [ 57 ]…”
Section: Emerging End Applications Of Magnetic Levitationmentioning
confidence: 99%
“…Median levitation height of circulating leukocytes was measured for 22 infected patients and 39 noninfected control patients, and it was observed that the levitation height was 293.1 AE 61.4 px for septic patients and 288.8 AE 23.7 px for the control group, demonstrating comparable classification performance of the developed MagLev platform. [57] A smartphone-based MagLev platform capable of detecting soluble and membrane-bound antigens, found in the blood, was developed to detect infectious diseases such as HBV s.a., EBV, HIV, HAV, Dengue, Zika, and Chikungunya. [108] This platform was successful in the detection of T-cell antigen CD3, RBC antigens CD35 and RhD, eosinophil antigen Siglec-8, soluble IL-6, and RBC-bound Epstein-Barr viral particles, while the detection performance was validated with immunofluorescence microscopy.…”
Section: Whole Blood Red Blood Cell and White Blood Cell Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Leukocyte is one of most important immune cells during sepsis. [6,7] Neutrophils were demonstrated that they played a crucial role in against pathogen during sepsis. [8,9] In addition, several studies showed lymphocyte apoptosis which induced immunosuppression during sepsis, [10][11][12] which was thought to be an important cause of death in patients with septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic levitation, which is levitating objects under an inhomogeneous magnetic field based on the balance of magnetic and buoyancy forces, has inspired many applications, including sorting numerous materials, the association of proteins and ligands, cell measurement and detection, 3D assembly of living cells, and biomarker detection. , Lately, this technology has emerged to provide high-throughput, compact, and portable analysis of microparticle and cell densities. ,, Fundamentals and applications of magnetic levitation are well documented in recent review articles. …”
mentioning
confidence: 99%